The quadrupole microelectrode design on a multilayer biochip for dielectrophoretic trapping of single cells - Ibrahim, Siti Noorjannah (Elsevier, 2011)
This paper introduces a new quadrupolemicroelectrodedesign for trapping mass loading of singlecells using dielectrophoretic (DEP) force. The DEP force profiles generated by the pattern which represent trapping regions on the biochip platform, were studied using finite element software Comsol Multiphysics v3.5a. Arrays of the quadrupolemicroelectrode were patterned on amultilayer structure called sandwiched insulator with back contact (SIBC) biochip platform, fabricated using photolithography technique. This platform consists of a 10 nm Nickel–Chromium (NiCr) and 100 nm Gold (Au) top electrode, 5 μm thick SU-8 2005 insulation layer and a bottom layer of 10 nm NiCr and 100 nm Au called the back contact. Access to the back contact is achieved via a microcavity located at the center of the quadrupolemicroelectrode arrangement. Together, the DEP forces generated from the quadrupolemicroelectrode and the microcavities are used to anchor singlecells and maintain cell positions. The quadrupoledesign was tested with polystyrene latex microbeads, and Ishikawa cancer cells suspended in media and flowed through microfluidic channels made from PDMS. Singlecelltrapping becomes evident when both quadrupolemicroelectrode and back contact are biased using AC potentials of different phases. Experiment results show that the quadrupolemicroelectrode trapped 22 percent of Ishikawa cancer cells and 17 percent of the polystyrene microbeads.